Prevalence and Pattern of Skin Disorder among Primaryschool Children in Wasit Governorate, Iraq, 2021 - Dr. Basim Abdulrazzaq Abood Algharbawi; Dr. Sundus Jaafar Mahmood Ai Baraznchi; Dr. Jawad Kadhim Mahdi Al-Mnehil (Zien Journals, 2023)
S Skin diseases account for a large portion of the worldwide sickness burden and are among the leading causes of non-fatal disease. Where skin problems are one of the most prevalent organ-specific reasons for people to attend the primary health care center; they are common in various nations, although the spectrum varies widely. This study aimed to study the prevalence and Pattern of Skin Disorders among Primary-school Children in Wasit Governorate, Iraq, 2021. Material and Methods: A cross-sectional study was carried out from October to December 2022. A multi-stage, stratified sampling procedure was used to choose ten elementary schools in Iraq's Wasit Governorate, five in urban regions and five in rural ones. In the second stage, 40 pupils were chosen at random from each school for a total sample size of 400. Results: The current study involved 400 individuals; males made up the majority of the participants (55%), and more than half of the participants (52.5%) resided in cities. Skin problems were seen in 45% of people. There was a strong link between the occurrence of skin problems and gender. Participants with a father and mother who had only completed basic school had a greater incidence. Conclusion: The prevalence of skin disorders among primary school children was 45%. The gender, father education, and mother education significantly affected the prevalence. Viral, fungal, and bacterial infections were the most common causes of skin disorders.
Keywords: Iraq; Skin disorder; Children; Primary school